Peranan Keputusan Hedging dalam Hubungan Risiko Nilai Tukar Rupiah dan Growth Opportunity terhadap Profitabilitas - Santoso, Gabriela; Rachmawati, Dyna (E-Jurnal Akuntansi; Vol 31 No 10 (2021)DO - 10.24843/EJA.2021.v31.i10.p19, 2021)
This study aims to examine and analyze the effect of the risk of rupiah exchange rate and growth opportunity on profitability with hedging decisions as moderating variables. The risk of rupiah exchange rate is measured by exchange rate exposure, growth opportunity is measured by comparing MVE and BVE, and hedging decisions are measured by the dummy method, and profitability by net profti margin. The object of research used is manufacturing companies listed on the IDX during 2017-2019 periods. The sample selection used purposive sampling. Data analysis used linear regression analysis technique and MRA. The results showed that the risk of rupiah exchange rate had no effect on profitability, hedging decisions reduced the negative effect of the risk of rupiah exchange rate on profitability, and growth opportunity had a positive effect on profitability. Keywords: Risk of Rupiah Exhange Rate; Growth Opportunity; Profitability; Hedging Decisions.